1983
DOI: 10.1007/bf00399316
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Candida famata and Trichosporon cutaneum on uric acid as the sole source of carbon and energy, a hitherto unknown property of yeasts

Abstract: Growth of Candida famata and Trichosporon cutaneum on uric acid as the sole source of carbon and energy, a hitherto unknown property of yeasts Middelhoven, W.J.; Brink, Jolanda A. van den; Veenhuis, M. Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.Downloaded from the University of Groningen/UMCG research database (Pure): http://www.rug.nl/research/portal. For technical reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
(3 reference statements)
0
14
0
Order By: Relevance
“…The growth medium supplemented with five antibacterial antibiotics was as described earlier (Middelhoven et al, 1983). However, the concentration of KH2PO4 was 20 g-1 -a instead of 1 g. 1-1 to increase the buffering capacity.…”
Section: Enrichment Culturesmentioning
confidence: 99%
See 3 more Smart Citations
“…The growth medium supplemented with five antibacterial antibiotics was as described earlier (Middelhoven et al, 1983). However, the concentration of KH2PO4 was 20 g-1 -a instead of 1 g. 1-1 to increase the buffering capacity.…”
Section: Enrichment Culturesmentioning
confidence: 99%
“…These phenomena have been considered from a taxonomic point of view (Hazeu et al, 1972;Bos and De Bruyn, 1973). Recently, utilization by some yeasts of uric acid (Middelhoven et al, 1983) and adenine (Middelhoven et al, 1984) as sole carbon source was demonstrated. All of these yeast strains were able to utilize some primary n-alkylamines, e.g.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Uric acid is one of these nonconventional substrates (Middelhoven et al 1983). Like other aerobic microorganisms, ascomycetous and a basidiomycetous yeast species degrade uric acid by oxidation to allantoin that, in three successive hydrolytic steps, is converted into 1 mol glyoxylate and 2 mol urea (Middelhoven et al 1983).…”
mentioning
confidence: 99%